Determination of interest rates in small open economies: A review of recent evidence - Matti Virén (Bank of Finland, 1988)
This paper examines the determination of interest rates in small open economies. We use the classical interest rate parity relationships as a starting point in developing a test procedure which allows us to evaluate the importance of various domestic shocks (in particular, monetary and fiscal shocks). This, in turn, gives us some estimates of the degree of monetary autonomy in the respective countries. The empirical analysis covers seven smal' European countries; the sample period is 1980Ml - 1981M12. The general result of this study is that the uncovered interest parity relationship is not sufficient to explain the movement in domestic interest rates, particularly in short-term rates.
URN:NBN:fi:bof-201807301744
Keywords: 330